1997
DOI: 10.1046/j.1464-410x.1997.30412.x
|View full text |Cite
|
Sign up to set email alerts
|

A potential autocrine loop between heregulin‐alpha and erbB‐3 receptor in human prostatic adenocarcinoma

Abstract: Objective To examine the expression of heregulin-alpha stained negatively for heregulin-alpha and erbB-3. Fourteen patients had bony metastases identified by (a new member of the epidermal growth factor family) and its receptor erbB-3 in human prostate cancer by bone scintigraphy and all received androgen ablation after undergoing transurethral resection of the prosimmunohistochemistry, and to analyse their implication for clinical outcome.tate. Immunoreactivity for heregulin-alpha and erbB-3 were absent in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 5 publications
4
42
0
Order By: Relevance
“…This report also indicates that biological responses to heregulin both in vitro and in vivo are directly correlated with HER-2/neu expression levels. This con®rms results from other investigators indicating that heregulin signaling through HER-3 and HER-4 may be dependent on HER-2/neu expression levels in breast (Riese et al, 1995;Beerli et al, 1995) as well as prostate cells (Leung et al, 1997;Grasso et al, 1997). The observed variability for the expression of the di erent RTK type I, in particular the changes in HER-3 number post HER-2 transfection, most likely have an impact on the extent of the e ect of HRG.…”
Section: Discussionsupporting
confidence: 88%
“…This report also indicates that biological responses to heregulin both in vitro and in vivo are directly correlated with HER-2/neu expression levels. This con®rms results from other investigators indicating that heregulin signaling through HER-3 and HER-4 may be dependent on HER-2/neu expression levels in breast (Riese et al, 1995;Beerli et al, 1995) as well as prostate cells (Leung et al, 1997;Grasso et al, 1997). The observed variability for the expression of the di erent RTK type I, in particular the changes in HER-3 number post HER-2 transfection, most likely have an impact on the extent of the e ect of HRG.…”
Section: Discussionsupporting
confidence: 88%
“…[260][261][262][263][264] Findings regarding NRG expression have been mixed. While NRG1 was expressed in the majority of prostate cancers as observed by immunohistochemistry, 252 other studies have found this ligand to be absent from prostate cancers 253 and malignant cell lines, 253,258 although expression of NRG in prostate stroma 253 and other cell types could have effects on cancers within the organ.…”
Section: Prostate Cancermentioning
confidence: 86%
“…[248][249][250] Furthermore, ERBB2/ERBB3 complexes caused AKT-independent phosphorylation of the androgen receptor that stabilized the protein and enhanced its transcriptional activity. 248 Increased expression of ERBB3 in prostate cancers, compared with normal prostate, has been demonstrated by immunohistochemistry in several studies 79,[251][252][253][254] and was associated with poor prognosis. 252 Microarray analyses have likewise shown an increase in ERBB3 mRNA in these cancers.…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies of the role of ErbB2 in clinical prostate cancer remain inconclusive (Grossmann et al, 2001), and initial clinical trials indicate that the anti-ErbB2 antibody Herceptin (trastuzumab) does not show significant clinical activity as a single agent (Ziada et al, 2004). ErbB3 has not been as extensively studied, but analysis of clinical prostate cancer specimens indicates that overexpression of ErbB3 has been linked to a less favourable prognosis (Leung et al, 1997).…”
mentioning
confidence: 99%